Participation of Social Media Influencers in Communicating the Global Health Crisis: An Observation of Chinese-Origin Influencers Across Argentina, the UK, and Spain During COVID-19 - Yiheng Wang; Felipe Navarro Nicoletti (Journalism and Media)
This work focuses on the digital communicative practices of influencers, as the COVID-19 pandemic has opened a communicational doorway from diverse perspectives, and social media has emerged as an important tool for people to maintain contact and acquire information. Additionally, the preventive and obligatory social distancing measures have driven us to reconsider methods of human interaction. Digital communication as the primary means of connection in the context of COVID-19 encompasses social interaction, entertainment, and informative channels. These facets usually coalesce within a single space or intersect when the practices of influencers are observed. Therefore, three influencers of Chinese origin residing in different countries are analysed, given that China was the initial epicentre of COVID-19. Influencers of Chinese descent living in the United Kingdom, Spain, and Argentina are selected to enable an exploration of more sociocultural diversity. The significance of influencers in disseminating information and content to society continues, according to observation, particularly among younger demographics. Although their main efforts do not reside in communicating COVID-19 within the context of the pandemic, their contribution indicates a complementary solution to fostering social interaction and debunking discourses of hatred aimed at individuals of Chinese or Asian descent.